COMBINING THE FORECAST AND FLEXIBLE BUDGETS. - Marple, R. P. (The Accounting Review, 1946)
Abstract Since business first adapted for its own use the budget idea which had been developed as a means of organizing and controlling the financial affairs of governments, several types or styles of budgets have been developed. To a limited extent, the appropriation type of budget common to governmental budgeting has been carried over into business. This type of budget involves the appropriation of a definite amount for a prescribed purpose and the limitation of expenditures to the amount appropriated. Based on a recognition of the difference between fixed and variable costs, the flexible or variable budget is a control device which recognizes that different expense allowances are necessary for different rates of activity. Comparison of the budget figures thus determined with the costs actually incurred provides a closer control than is possible when the cost allowances are based on forecast volumes which differ from the volumes actually attained. The flexible budget idea has been applied principally to the control of departmental overhead.